Implementation of Automatic Irrigation and Assistance in Packaged Sambal Production at KWT Mawar I - Pranoto, Sarwo; Asnawi, Rustam; Ratnaningsih, Nani (JPPM (Jurnal Pengabdian dan Pemberdayaan Masyarakat), 2025)
KWT Mawar I is a farmer group focused on agricultural activities, primarily vegetable farming, located in Ngentak, RT 01, Bangunjiwo, Kasihan, Bantul. This group was established by the community to meet food needs by utilizing household yards. Officially recognized by the subdistrict government on December 25, 2022, KWT Mawar I operates as a community-driven initiative. However, it faces several challenges, including a manual irrigation system, limited knowledge of post-harvest processing, and constrained marketing strategies for their produce. The goal of the PKM (Community Service Program) is to address these issues through socialization and guidance in creating packaged sambal products, implementing appropriate technology using the Internet of Things (IoT) and Renewable Energy (RE), and leveraging social media for marketing. The program aims to equip the group with skills in packaged sambal production, the application of appropriate technology for land irrigation, and effective product marketing via social media. The methods employed in the PKM program include socialization, discussions, and training sessions. The expected outcomes of the PKM program are increased knowledge of chili post-harvest processing, the adoption of IoT-based automated irrigation systems for KWT Mawar I’s land, and the effective use of social media to market their processed products.